(untitled) (Research, Society and Development, 2022)
This paper analyzes composition procedures in the areas of text and discourse in multiliteracy practices in the early teacher education and investigatives netnographic actions (professional) in the view of academic and teaching literacies development as well as digital multiliterate practices in processes of writing, by people from the Language Portuguese Course, from the in the presential modality. The corpus of analysis is compound by commentaries and textual composition (opinion articles) from students of the first module of the project “From the usual writing to the screen: multiliterate inter-actions in the teacher formative process” (PIBIC research). The methodology included four steps. The first was (i) reading and discussion of the theoretical framework, (ii) drafting an invitation, then (iii) minicourse divulgation, at last, (iv) definition about module’s steps, elaborated in a total of 4 weeks. As a method of investigation, in a qualitative perspective of research in education, we chose the action research, with a collaborative scope. As a research method, in a qualitative perspective of research in education, there has been chosen the research-action. The study has confirmed the need of promoting online events which foster teaching practices that constantly need ressignifications. We have been developing actions that have led us to the contemplation of some categories that are text and discourse related in multiliterate virtual environments, affiliated to netnographic studies.